The antifungal pipeline: the need is established. Are there new compounds?. Issue 4 (30th April 2020) - Li, Dongmei; She, Xiaodong; Calderone, Richard
ABSTRACT: Our review summarizes and compares the temporal development (eras) of antifungal drug discovery as well as antibacterial ventures. The innovation gap that occurred in antibacterial discovery from 1960 to 2000 was likely due to tailoring of existing compounds to have better activity than predecessors. Antifungal discovery also faced innovation gaps. The semi-synthetic antibiotic era was followed closely by the resistance era and the heightened need for new compounds and targets. With the immense contribution of comparative genomics, antifungal targets became part of the discovery focus. These targets by definition are absolutely required to be fungal- or even lineage (clade) specific. Importantly, targets need to be essential for growth and/or have important roles in disease and pathogenesis. Two types of antifungals are discussed that are mostly in the FDA phase I–III clinical trials. New antifungals are either modified to increase bioavailability and stability for instance, or are new compounds that inhibit new targets. One of the important developments in incentivizing new antifungal discovery has been the prolific number of publications of global and country-specific incidence. International efforts that champion global antimicrobial drug discovery are discussed. Still, interventions are needed. The current pipeline of antifungals and alternatives to antifungals are discussed including vaccines. Abstract : This review covers the eras of antimicrobial discovery, antifungals and targets, and key players in future developments.